The diversity of bacterial conjugation and mobilization systems - de la Cruz, Fernando (Henry Stewart Talks, 2008)
Transfer of DNA between bacterial cells, Basic plasmid platforms, The mechanism and key components of conjugation, The mating channel, The complex between TrwC and its substrate DNA, The relaxosome, The diversity of relaxases, The IncW family, Methods for plasmid classification, Plasmid MOB families, The NCBI plasmid database, Plasmid sequencing